DEPRESI, ANSIETAS, STRES PADA CAREGIVER INFORMAL LANSIA PENYAKIT KRONIS - Monika Luhung; Elizabeth Yun Yun Vinsur (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIKes Panti Waluya Malang, 2023)
Background: The number of elderly people with chronic diseases continues to increase and the decline in body function experienced means that elderly people need help from other people in meeting their daily needs. In the context of family culture in Indonesia, elderly people are still found living with their children, grandchildren, nieces, nephews, in-laws, or other family members who act as informal caregivers. Informal caregivers make a positive contribution to the health of the elderly, but on the other hand, sudden and unprepared changes in roles result in psychological problems. Objective: The research aims to identify psychological problems: depression, anxiety, stress of informal caregivers who care for elderly people with chronic illnesses. Method:A descriptive-analytical study with a cross-sectional approach. The research population was all informal caregivers for elderly people with chronic illnesses in RW 1, Sukoharjo Village, the working area of the Bareng Community Health Center, Malang, totaling 49 respondents. The sampling technique used was total sampling. Data collection was carried out by survey using the DASS 42 instrument. Result:The level of depression in the normal category was 95.9%, and the mild category was 4.1%, the level of anxiety without anxiety was 85.7%, and the stress level showed 100% of informal caregivers in the normal stress category. Conclusion: The psychological problems of elderly caregivers are classified as normal or very low. Caregivers need to be aware of changes in the condition of the elderly which have an impact on their independence, where the duration of time caregivers carry out caregiving is at risk of increasing and increasing the risk of increased depression, anxiety and stress experienced by informal caregivers. Keywords: Informal caregiver; DASS 42; Elderly; Chronic illness